Real Time Panoramic Video in OpenCV using Image Stitching Techniques - Rajasri, K; Gayathri, D; Ilanthirayan, Balasundari; Sundra, A (International Journal of Computer Sciences and Engineering, 2025)
Image stitching is basically integrating two or more images to form a single panorama. This process of integrating can be performed by overlapping the images contains common scenes. The panoramic stitching of images is widely used for virtual reality photography and 360 degree cameras. Now a day, panoramic video has also gained importance over a period of time. It has many application built in over it such as security, surveillance, computer vision, robotics, virtual reality and much more. Generation panoramic video can be divided into many steps namely extracting frames from the input video from variety of multiple devices, web-cam etc., time synchronizing the extracted frames, stitching frame to create panoramic frames and then combines those panoramic frames into video. An off-line video of such panoramic frame could be made since there is no time constraint. However generating real time panoramic video is more challenging because of computation resources required and optimization required to produce panoramic real time video. This paper describes the concept of generating real time panoramic video. It also uses the image stitching methods to generate the panorama with the help of Open CV. We are proposing to develop such application which will be very useful in security and surveillance.